2017
DOI: 10.21037/cdt.2017.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected evolution of a non-stenotic lesion in the left main coronary artery of a patient with non–ST-segment elevation myocardial infarction

Abstract: A 72-year-old man was referred to our catheterization laboratory 48 hours after a non-ST-segment elevation myocardial infarction. His medical history included coronary artery disease (CAD) (percutaneous coronary intervention of the right coronary artery and chronic total occlusion of the circumflex artery), atrial fibrillation (AF), and chronic kidney disease. An electrocardiogram showed a pre-existent left bundle-branch block and the patient's maximum cardiac troponin concentration was 8.64 µg/L (upper limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…rombosis is one of the main causes of myocardial infarction in CAAs. Ispas et al [11] used aspirin combined with warfarin for the 2 Case Reports in Medicine patients with left main aneurysm stents at long durations. A recent study also suggested a possible advantage of anticoagulation in patients with CAAs and acute coronary syndrome [12].…”
Section: Discussionmentioning
confidence: 99%
“…rombosis is one of the main causes of myocardial infarction in CAAs. Ispas et al [11] used aspirin combined with warfarin for the 2 Case Reports in Medicine patients with left main aneurysm stents at long durations. A recent study also suggested a possible advantage of anticoagulation in patients with CAAs and acute coronary syndrome [12].…”
Section: Discussionmentioning
confidence: 99%
“…There are minimal published data on the use of these devices as outlined in Table 2, with the majority of experience in small case series or case reports of coronary artery perforation 16,18 and coronary artery aneurysm and fistula treatment. 17,[19][20][21] There are no reported cases of the use of these devices in the treatment of saphenous vein graft aneurysm.…”
Section: Casementioning
confidence: 99%
“…After coronary heart disease develops into AMI, the mortality rate of patients may be significantly increased if they are complicated with atrial fibrillation. At present, revascularization can be performed effectively via percutaneous coronary intervention (PCI) for AMI patients complicated with atrial fibrillation, ensuring the reperfusion of ischemic myocardium ( 6 ). However, there are few literature studies on the effect of atrial fibrillation (new-onset or complicated previously) on the prognosis of patients receiving PCI after MI.…”
Section: Introductionmentioning
confidence: 99%